1993
DOI: 10.1073/pnas.90.14.6791
|View full text |Cite
|
Sign up to set email alerts
|

On how a myosin tryptophan may be perturbed.

Abstract: A weil-known indication that a nucleotide has bound to myosin Is the enhancement of the fluorescence of a speciflc tryptophan in the "subfragment 1" segment of the protein. Empirically the effect has been enormously useful in myosin enzymology. But beyond an early suggestion that it aries from a purine-tryptophan charge-transfer complex, the mechanism of the effect has not been considered. Here we consider the alternative that it arises from an Ionizable group (either another residue or the phosphate of the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The exact reason for the fluorescence enhancement cannot be explained by the present structures since it is likely that the exact nature of the conformational change that occurs around Trp 501 is influenced by the essential light chain which is missing from the structures of S1Dc. It has been suggested that the fluorescence enhancement might be due to an interaction between an ionizable side chain and the indole ring (Bivin et al, 1993). The use of the ADP,Vi complex to account for the fluorescence enhancement must also be qualified by the observation that in rabbit skeletal muscle myosin the ADP,Vi complex shows a lower level of 8 were prepared with the programs FRODO and MOLVIEW (Jones, 1985;Smith, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The exact reason for the fluorescence enhancement cannot be explained by the present structures since it is likely that the exact nature of the conformational change that occurs around Trp 501 is influenced by the essential light chain which is missing from the structures of S1Dc. It has been suggested that the fluorescence enhancement might be due to an interaction between an ionizable side chain and the indole ring (Bivin et al, 1993). The use of the ADP,Vi complex to account for the fluorescence enhancement must also be qualified by the observation that in rabbit skeletal muscle myosin the ADP,Vi complex shows a lower level of 8 were prepared with the programs FRODO and MOLVIEW (Jones, 1985;Smith, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Isolation of ASTs Other than Trp510. Trp510 is a known AST (9)(10)(11)(12)29). The possibility that the ASTs include residues other than Trp510 was considered using 5′IAF to specifically modify SH1 in S1.…”
Section: Resultsmentioning
confidence: 99%
“…Tryptophan emission intensity from S1 is altered by ATP binding to its active site (Werber et al, 1972). Trp510 is one of the ATP-sensitive tryptophans (Johnson et al, 1991;Hiratsuka, 1992;Bivin et al, 1993;Papp & Highsmith, 1993;Park et al, 1996b,c). The nucleotide-sensitive tryptophan emission showed that the stable complexes of ADP with vanadate, beryllofluoride, or aluminofluoride bound to S1 mimic ATPase intermediates (Werber et al, 1992).…”
Section: Discussionmentioning
confidence: 99%